Combination of subtotal pneumofibrosis and post-COVID pulmonary complications in the context of the progression of systemic sclerosis (clinical observation) - M. V. Mnikhovich; A. A. Soldatova; I. A. Shiripenko; O. А. Sidorova; M. V. Lozina; S. V. Snegur; Yu. G. Pavlova; P. P. Baklanov; D. D. Kaminer (Современная ревматология)
We present a clinical case of the development of subtotal pneumofibrosis associated with the progression of systemic sclerosis in a patient previously infected with COVID-19. Investigating the possible relationship between these conditions is important both for understanding the current therapeutic algorithm and for further aetiopathogenetic studies on the nature of rheumatic diseases.